3D Printing of Flexible Strain Sensor Array Based on UV‐Curable Multiwalled Carbon Nanotube/Elastomer Composite. Issue 1 (20th November 2020) - Xiao, Ting; Qian, Cheng; Yin, Ruixue; Wang, Kemin; Gao, Yang; Xuan, Fuzhen
Abstract: Internet of things (IoT) is expected to significantly improve every aspect of society, especially in soft robotics, structural health monitoring, and human motion detection. Flexible strain sensors with high‐performance characteristics as well as highly efficient and cost‐effective maskless fabrication methods are the key components of IoT for these applications. Herein, a 3D printing technology using digital light processing is developed to fabricate high‐performance flexible strain sensors based on UV‐curable multiwalled carbon nanotubes/elastomer (MWCNT/EA) composite. The MWCNT/EA‐based device with 2 wt% MWCNTs delivers a sensitivity of 8.939 with a linearity up to 45% strain. Additionally, the sensor has a detectable strain range from 0.01% to 60%, a high mechanical durability (10 000 cycles), and linear responses to humidity and temperature. Numerical simulation and impedance study indicate that the sensor works on the deformation‐induced reduction of MWCNT conductive pathway. The developed device can be used to detect various external deformation, when combined with a near‐field communication circuit. Moreover, a 4 × 4 strain sensor array is developed for sensing external stimuli distribution, further demonstrating the high performance of the 3D printed device. Abstract : A high performance strain sensor array is fabricated by digital light processing technology, with a sensitivity of 8.939 and a linearity up to 45% strain. Numerical simulation and impedance study indicate that the sensor works on the deformation‐induced reduction of active material conductive pathway. The device can monitor various external stimuli, with the capability of wireless data transmission.